2007
DOI: 10.1186/cc5671
|View full text |Cite
|
Sign up to set email alerts
|

Simplified electrophysiological evaluation of peripheral nerves in critically ill patients: the Italian multi-centre CRIMYNE study

Abstract: IntroductionCritical illness myopathy and/or neuropathy (CRIMYNE) is frequent in intensive care unit (ICU) patients. Although complete electrophysiological tests of peripheral nerves and muscles are essential to diagnose it, they are time-consuming, precluding extensive use in daily ICU practice. We evaluated whether a simplified electrophysiological investigation of only two nerves could be used as an alternative to complete electrophysiological tests.MethodsIn this prospective, multi-centre study, 92 ICU pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(72 citation statements)
references
References 48 publications
7
64
0
1
Order By: Relevance
“…Mortality in our study (2.5%) was in line with previous results from a literature review suggesting no increase of unadjusted mortality in critical ill patients with neuromuscular abnormalities [9]. However, other studies revealed a higher mortality between 21 and 55% among CIP and CIM patients [1012], in particular with coincident sepsis [16, 17]. …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Mortality in our study (2.5%) was in line with previous results from a literature review suggesting no increase of unadjusted mortality in critical ill patients with neuromuscular abnormalities [9]. However, other studies revealed a higher mortality between 21 and 55% among CIP and CIM patients [1012], in particular with coincident sepsis [16, 17]. …”
Section: Discussionsupporting
confidence: 91%
“…Most frequently, neurography of peroneal and sural nerves have been analyzed in CIP [1012]. Our data confirmed the importance and sensitivity of peroneal nerve measurements [10].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations